Human Progress Towards Equitable Sustainable Development – part II: Empirical Exploration - Udo, Victor; Pawłowski, Artur (Problemy Ekorozwoju, 2011)
The paper propose an empirical definition of sustainable development, which is used for detailed conceptualization and operationalization into an index for comparing national polities. Patterns/gaps of sustainable development index performance among national polities using a sample of 132 countries are explored comparatively based on readily available secondary data. Finally, the fractal-based framework is used to make concluding observations and discussions regarding national polities performance on sustainable development as an index of social sustainability, technological sustainability and environmental sustainability indications.